Makna Simbolik Pratima Hyang Ratu di Pura Dadia Se-Desa Adat Kerobokan Kabupaten Badung - Ni Nyoman Sri Widiasih; I Gede Rudia Adiputra; I Nyoman Kiriana (Jurnal Penelitian Agama Hindu, 2022)
The existence of Hindus in the world cannot be separated from the use of media or symbols to worship God, one of which is pratima (in Balinese it is called pretima). Pratima Hyang and Ratu, when viewed from the history of the development of the art of sculpture, the paired statues (husband and wife) can be suspected as the embodiment of the spirits of the kings as rulers of the region, while Pratima Hyang can be suspected as the oracle of Hyang Widhi'sbecause the prestigepralingga used is in the form of an ox that can be used as an ox. identified with the prebhawa Hyang Widhi, namely Dewa Iswara riding a white ox. This research using descriptive qualitative methods. The approach used in this research is the approach Exfost facto. The theory used in this research is a symbol theory. This type of data and research are primary data and secondary data. The symbolic meanings of pratima Hyang and Ratu include: a) the meaning of holiness, meaning that by worshiping and honoring pratima Hyang and Ratu in the temple, it is expected to awaken and maintain the sanctity of the hearts of the worshipers; b) the meaning of the leadership of pratima Ratu with the title Ratu means to lead, it is hoped that the worshipers of pratima and the temple concerned are able to lead their deities in an effort to strengthen and increase srada bhakti to the gods and ancestors; c) the meaning of harmony and unity means that through the existence of pratima Hyang and Ratu, it can grow, awaken, and strengthen the spirit of harmony of the people who carry the pratima and the temple concerned.